Genetic Deletion of TREK-1 or TWIK-1/TREK-1 Potassium Channels does not Alter the Basic Electrophysiological Properties of Mature Hippocampal Astrocytes In Situ - Du, Yixing; Kiyoshi, Conrad M.; Wang, Qi; Wang, Wei; Ma, Baofeng; Alford, Catherine C.; Zhong, Shiying; Wan, Qi; Chen, Haijun; Lloyd, Eric E.; Bryan, Robert M. Jr.; Zhou, Min (Frontiers in Cellular Neuroscience, 2016)
We have recently shown that a linear current-to-voltage (I-V) relationship of membrane conductance (passive conductance) reflects the intrinsic property of K+ channels in mature astrocytes. While passive conductance is known to underpin a highly negative and stable membrane potential (VM) essential for the basic homeostatic function of astrocytes, a complete repertoire of the involved K+ channels remains elusive. TREK-1 two-pore domain K+ channel (K2P) is highly expressed in astrocytes, and covalent association of TREK-1 with TWIK-1, another highly expressed astrocytic K2P, has been reported as a mechanism underlying the trafficking of this heterodimer channel to the membrane and contributing to astrocytes’ passive conductance. To decipher the individual contribution of TREK-1 and address whether the appearance of passive conductance is conditional to the co-expression of TWIK-1/TREK-1 in astrocytes, TREK-1 single and TWIK-1/TREK-1 double gene knockout mice were used in the present study. The relative quantity of mRNA encoding other astrocyte K+ channels, such as Kir4.1, Kir5.1, and TREK-2, was not altered in these gene knockout mice. Whole-cell recording from hippocampal astrocytes in situ revealed no detectable changes in astrocyte passive conductance, VM, or membrane input resistance (Rin) in either kind of gene knockout mouse. Additionally, TREK-1 proteins were mainly located in the intracellular compartments of the hippocampus. Altogether, genetic deletion of TREK-1 alone or together with TWIK-1 produced no obvious alteration in the basic electrophysiological properties of hippocampal astrocytes. Thus, future research focusing on other K+ channels may shed light on this long-standing and important question in astrocyte physiology.